Initiation of vericiguat and short-term cardiovascular function improvement in heart failure patients with and without worsened renal function - Zhang, Xinyu; Zhou, Wei; Liu, Hui; Zhang, Chengquan; Qi, Yifan; Yuan, Xiao; Yuan, Zuyi; Sun, Lizhe; She, Jianqing; Lou, Bowen (Frontiers in Cardiovascular Medicine, 2025)
BackgroundRecognized as a global health issue, Heart failure (HF) is a complex clinical syndrome and often worsening due to cardiorenal interactions. vericiguat, a novel soluble guanylate cyclase (sGC) stimulator, is approved for treating heart failure (HF) with reduced ejection fraction (HFrEF). This study aims to assess the short-term improvement in cardio-function resulting from in-hospital initiation of vericiguat among patients with renal dysfunction.MethodsWe conducted a single-center, retrospective cohort study encompassing 401 consecutive HF patients admitted from January 2023 to June 2024, who initiated vericiguat treatment post-admission. Following propensity score matching (PSM), the study cohort was refined to 217 patients, categorized into three groups based on renal function: 31 with severe renal dysfunction, 62 with moderate renal dysfunction, and 124 with normal renal function. All patients received oral vericiguat, with the primary endpoint being the incidence of three major cardiovascular adverse events (3P-MACE) within one year. The secondary endpoint evaluated the change in left ventricular ejection fraction (LVEF) after six months relative to baseline.ResultsAfter six months of vericiguat therapy, a significant overall improvement in LVEF was observed (mean increase of 11.8%, p < 0.001). The severe renal dysfunction group demonstrated the most pronounced increase in LVEF (20.2%, p = 0.044), whereas the normal renal function group exhibited the most significant statistical improvement (10.9%, p < 0.001). Kaplan–Meier survival analysis revealed a markedly lower survival probability for the severe renal dysfunction group compared to the other groups (p < 0.001). The Cox proportional hazard regression model indicated a trend toward a higher risk of cardiovascular adverse events in the severe renal dysfunction group, which approached statistical significance after adjustments (HR = 137.64, p-value = 0.050).ConclusionVericiguat enhances cardiac function in HF patients, irrespective of renal function status, and merits further investigation for the optimization of treatment strategies in HF patients with renal comorbidities.Clinical Trial Registrationclinicaltrials.gov, identifier (Unique Protocol ID: 82100477-3).